Direct or subacute coronary angiography in out-of-hospital cardiac arrest (DISCO)—An initial pilot-study of a randomized clinical trial. (June 2019) - Elfwén, Ludvig; Lagedal, Rickard; Nordberg, Per; James, Stefan; Oldgren, Jonas; Böhm, Felix; Lundgren, Peter; Rylander, Christian; van der Linden, Jan; Hollenberg, Jacob; Erlinge, David; Cronberg, Tobias; et al.
Abstract: Background: The clinical importance of immediate coronary angiography, with potentially subsequent percutaneous coronary intervention (PCI), in out-of-hospital cardiac arrest (OHCA) patients without ST-elevation on the ECG is unclear. In this study, we assessed feasibility and safety aspects of performing immediate coronary angiography in a pre-specified pilot phase of the 'DIrect or Subacute Coronary angiography in Out-of-hospital cardiac arrest' (DISCO) randomized controlled trial (ClinicalTrials.gov ID: NCT02309151). Methods: Resuscitated bystander witnessed OHCA patients >18 years without ST-elevation on the ECG were randomized to immediate coronary angiography versus standard of care. Event times, procedure related adverse events and safety variables within 7 days were recorded. Results: In total, 79 patients were randomized to immediate angiography (n = 39) or standard of care (n = 40). No major differences in baseline characteristics between the groups were found. There were no differences in the proportion of bleedings and renal failure. Three patients randomized to immediate angiography and six patients randomized to standard care died within 24 h. The median time from EMS arrival to coronary angiography was 135 min in the immediate angiography group. In patients randomized to immediate angiography a culprit lesion was found in 14/38 (36.8%) and PCI was performed in all these patients. In 6/40 (15%) patients randomized to standard of care, coronary angiography was performed before the stipulated 3 days. Conclusion: In this out-of-hospital cardiac arrest population without ST-elevation, randomization to a strategy to perform immediate coronary angiography was feasible although the time window of 120 min from EMS arrival at the scene of the arrest to start of coronary angiography was not achieved. No significant safety issues were reported.